Performance monitoring and stop signal inhibition in abstinent patients with cocaine dependence - Li, Chiang-shan Ray; Milivojevic, Verica; Kemp, Kathleen; Hong, Kwangik; Sinha, Rajita (Drug and alcohol dependence, 2006)
Impulsivity has been associated with drug abuse and relapse. As a measure of impulsivity, response inhibition in a stop signal task is impaired in substance abusers compared to healthy control subjects. However, cognitive processes besides response inhibition can affect performance in the stop signal task. Greater response readiness to the go signal increases stop signal reaction time (SSRT) and greater performance monitoring elicited by the stop signal decreases SSRT. Prolonged SSRT, therefore, may reflect differences in these other task-related cognitive processes rather than impaired response inhibition. Using a tracking stop-signal task, we compared 18 abstinent cocaine dependent patients with 41 age- and education-matched healthy controls. We computed SSRT for each individual subject on the basis of the horse race model. We also computed the fore-period (FP) effect to measure response readiness to the go signal and the post-signal slowing (PSS) effect to measure performance monitoring to the stop signal. Cocaine subjects showed increased SSRT and decreased PSS effect, compared to healthy controls. Covariance adjustment for the PSS effect eliminated the SSRT difference from healthy controls. These results suggest that diminished performance monitoring can be a critical cognitive mechanism underlying impaired response inhibition in cocaine dependent patients.